Characterisation of water hyacinth with microwave-heated alkali pretreatment for enhanced enzymatic digestibility and hydrogen/methane fermentation. (April 2015) - Lin, Richen; Cheng, Jun; Song, Wenlu; Ding, Lingkan; Xie, Binfei; Zhou, Junhu; Cen, Kefa
Highlights: Microwave-heated alkali pretreatment (MAP) was effective to pretreat water hyacinth. MAP resulted in a deconstructed lignocellulose matrix and swollen surface. Crystallinity decreased from 16.0 to 13.0 after MAP due to cellulose amorphisation. The energy conversion efficiency was enhanced to 49.5% by methane fermentation. Abstract: Microwave-heated alkali pretreatment (MAP) was investigated to improve enzymatic digestibility and H2 /CH4 production from water hyacinth. SEM revealed that MAP deconstructed the lignocellulose matrix and swelled the surfaces of water hyacinth. XRD indicated that MAP decreased the crystallinity index from 16.0 to 13.0 because of cellulose amorphisation. FTIR indicated that MAP effectively destroyed the lignin structure and disrupted the crystalline cellulose to reduce crystallinity. The reducing sugar yield of 0.296 g/gTVS was achieved at optimal hydrolysis conditions (microwave temperature = 190 °C, time = 10 min, and cellulase dosage = 5 wt%). The sequentially fermentative hydrogen and methane yields from water hyacinth with MAP and enzymatic hydrolysis were increased to 63.9 and 172.5 mL/gTVS, respectively. The energy conversion efficiency (40.0%) in the two-stage hydrogen and methane cogeneration was lower than that (49.5%) in the one-stage methane production (237.4 mL/gTVS) from water hyacinth with MAP and enzymatic hydrolysis.